Strategi Pengembangan Ekowisata Taman Wisata Alam Punti Kayu Kecamatan Alang-Alang Lebar Kota Palembang - M Syafrul Rasidin Safrul; Saraswati (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Several cities in Indonesia have implemented ecotourism as a tourist destination that sells nature. Like one of the City Forest Parks located in Palembang City, the park is called Punti Kayu which already existed and was built by the Dutch Government in 1936. Before becoming Punti Kayu, it was formerly called Taman Syailendra and was changed to Punti Kayu until now. The reason for the construction of Punti Kayu is to become a water catchment area. Punti Kayu City Forest Park has been approved as a Nature Tourism Park based on a conservation area that can be used as a City Forest tourist attraction. The land area of Punti Kayu has decreased from year to year from 98 hectares to 48 hectares until in 2002 Punti Kayu was legalized as a Nature and Conservation Tourism Park with an area of 39.9 hectares. for 2 years the world has been hit by the Covid-19 pandemic, causing losses to all mankind, including in the field of tourism. In this case, research was conducted to find out the current condition of the Punti Kayu Nature Park and how the researchers attempted to formulate a development strategy to anticipate land reduction and develop the Punti Kayu Nature Park so that it could attract many tourists to visit. The approach method used in this study is the combined method or Mix Method. The analytical method that researchers use is qualitative and quantitative analysis. Qualitative analysis itself was carried out by interviews, observation, data collection from previous researchers. Quantitative analysis that researchers do by using SWOT. The results of this research are expected to be a recommendation for a Development Strategy for the management to continue to develop Punti Kayu Abstrak. Beberapa Kota di Indonesia sudah menerapkan Ekowisata sebagai salah satu destinasi wisata yang menjual alam. Seperti salah satu Taman Hutan Kota yang terletak di Kota Palembang, Taman tersebut bernama Punti Kayu yang sudah ada dan dibangun Pemerintah Belanda pada Tahun 1936. Sebelum menjadi Punti Kayu dulunya bernama Taman Syailendra dan diubah menjadi Punti Kayu hingga sekarang. Alasan dibangunnya Punti Kayu untuk menjadi daerah resapan air. Taman Hutan Kota Punti Kayu sudah disahkan menjadi Taman Wisata Alam berbasiskan daerah konservasi yang bisa dimanfaatkan sebagai objek wisata Hutan Kota. Luas lahan Punti Kayu mengalami pengurangan dari tahun ke tahun dari luas lahan 98 Ha menjadi 48 Ha hingga pada tahun 2002 Punti Kayu di sahkan sebagai Taman Wisata Alam dan Konservasi dengan luas 39,9 Ha. selama 2 tahun Dunia dilanda pandemi Covid-19 sehingga menyebabkan kerugian seluruh umat manusia tak terkecuali dalam bidang pariwsata. Pada kasus ini diadakan penelitian untuk mengetahui kondisi terkini dari Taman Wisata Alam Punti Kayu serta bagaimana upaya peneliti dalam merumuskan sebuah strategi pengembangan untuk mengantisipasi terjadinya pengurangan lahan serta mengembangkan Taman Wisata Alam Punti Kayu agar bisa menarik banyak wisatawan untuk berkunjung. Metode pendekekatan yang digunakan dalam penelitian ini adalah metode gabungan atau Mix Method. Metode analisis yang peneliti gunakan adalah analisis kualitatif dan kuantitatif. Analisis kualitatif sendiri dilakukan dengan wawancara, observasi, pengumpulan data dari peneliti sebelum. Analisis kuantitatif yang peneliti lakukan dengan cara memakai SWOT. Hasil dari penelitian ini diharapkan bisa menjadi rekomendasi Strategi Pengembangan bagi pihak pengelola untuk terus mengembangkan Punti Kayu